The impact of mergers on the degree of competition in the banking industry - Vittoria Cerasi; Barbara Chizzolini; Marc Ivaldi (Fondazione Eni Enrico Mattei (FEEM), 2010)
This paper analyses the relation between competition and concentration in the banking sector. The empirical answer is given by testing a monopolistic competition model of bank branching behaviour on individual bank data at county level (départements and provinces) in France and Italy. We propose a measure of the degree of competiveness in each local market that is function also of market structure indicators. We then use the econometric model to evaluate the impact of horizontal mergers among incumbent banks on competition and discuss when, depending on the pre-merger structure of the market and geographic distribution of branches, the merger is anti-competitive. The paper has implications for competition policy as it suggests an applied tool to evaluate the potential anti-competitive impact of mergers.
Keywords: G21; L13; L59; 330; Banking Industry; Competition and Market Structure; Merger Policy